Yeraltı Suyu Kira Sözleşmeleri - (:unkn) unknown (My University, 2017)
Yeraltı suları, Anayasa'nın 168. maddesi kapsamında Tabii Servet ve Kaynaklar içerisinde yer almaktadır. Bu bakımdan, Devletin Hüküm ve Tasarrufu altında bulunan yer altı suları, sahipsiz kamu malları arasında kabul edilmektedir. Yeraltı sularının araştırılması, kullanılması, korunması ve tescili, 167 sayılı Yeraltı Suları Hakkında Kanununda düzenlenmiştir. Kanunun 4. maddesi gereğince, yeraltı suları il özel idarelerince kiraya verilir. Özel hukuk kişisi ile idare arasında imzalanan sözleşmenin konusunu kamu malı oluşturmaktadır. Bu nedenle, özel hukuk kişisi ile idare arasındaki hukuki ilişkinin, kamu hukukuna mı tabi yoksa özel hukuka mı tabi olduğunu tespit etmek gerekmektedir. Bu makalede, yeraltı sularının hukuki niteliği, yeraltı suları kira sözleşmelerinin imzalanmasına ilişkin ihale süreci ve yeraltı suları kira sözleşmesinin hukuki niteliğine ilişkin konular incelenmiştir

Ground waters are included in the scope of Natural Wealth and resources pursuant to Article 168 of Constitution. In this respect, ground waters shall be under the authority and at the disposal of the state and it is regarded as ownerless goods. Ground waters’ exploration, use, preservation and registration is regulated by Ground Water Law ( No:167). According to Article 4 of Groundwaters Law, it could be lease by special provincial administration. The subject-matter of the contract signed between the private legal person and the administration constitutes the public good. Therefore, it is necessary to determine whether the legal relationship between the private legal person and the administration is subject to public law or private law. In this study, legal status of groundwaters, procurement process relating to signing of groundwaters leasing contract, matters relating to legal status of groundwaters leasing contract were examined
Keywords: Hukuk